CHILDHOOD, GENDER, AND HEALTH PROMOTION: EDUCATIONAL INTERFACES IN CHILD CARE - dos Santos Leite, Tais; Cordeiro da Silva, Andrea; Neves Cavalcante Nascimento, Gabriela; Pereira da Silva, Esther; Abrantes Paletot, Yolanda; Nelson Martins Júnior, Leonidas (Revista Gênero e Interdisciplinaridade, 2026)
This article analyzes the interfaces between childhood, gender, and health promotion through a narrative literature review, focusing on educational experiences aimed at comprehensive child care. Published works from 2020 to 2025 that address intersectoral actions in the field of health education, considering the child as a subject of rights and a producer of culture, were selected. The discussion was organized into two thematic categories: (1) intersectoral educational actions in child health promotion and (2) gender and childhood: stereotypes, vulnerabilities, and educational strategies. The results indicate that intersectoral educational practices sensitive to diversity generate positive impacts on children’s autonomy, self-care, and socialization. Furthermore, they reveal that promoting health in childhood requires confronting gender stigmas present in educational and health institutions. It is concluded that comprehensive child care demands pedagogical strategies based on dialogue, active listening, and the valuing of differences, articulating education, health, and equity from early childhood.